Does The Paylater Usage In E-commerce Influence Gen Z’s Impulse Buying Behavior In Banjarmasin - Fatimah Azzahra; Annisa Sayyid (IAEI, 2023)
Payment methods that were previously limited to cash, paper-based, and card-based transactions are starting to be replaced by electronic payment systems as a result of the growth of e-commerce. Paylater is an electronic-based payment method on credit. Paylater is one of the triggers for impulse buying behavior.This study aims to determine the effect of using pay later on the impulse buying behavior of Gen Z’s who use e-commerce in Banjarmasin City. This research uses quantitative descriptive analysis and simple linear regression tests. The results of this study state that pay later affects the impulse buying behavior of Gen Z’s in Banjarmasin city. From this research, Gen Z should be wiser in using paylater. This study contributes to the literature about Gen’s impulse buying behavior in Banjarmasin.